Effect of Delegative Leadership on Achievement Motivation and Continuous Commitment - Vicky Achmad Zulfikar; Robbi Saepul Rahman (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2019)
The research aims to determine the effect of delegative leadership on achievement motivation and continuous commitment. Base on previous studies prove that delegative leadership is part of the situational leadership style, but generally, this delegative leadership use approach through traits, behaviors, how, processes, and situation. In this study, it is using instruments based predictors that determine the delegation, which has been validated and replicated right on this study and can use in the area of Bandung. Likewise, this research proves that achievement motivation that adopts from the Mcclelland achievement motivation instrument and examines the continuous commitment taken from Allen & Meyer can be replicated. In the first phase correlation analysis to the delegation, competence, fitness for purpose, time together, the level of work and LMX were significant predictors of delegation, at the second stage of the analysis of the correlation between leadership delegative, achievement motivation and commitment continuous show the relationship that significant. Still, partial report on continuous commitment does not have the support of the relationship from competence and sharing time. In the third stage, the (simultaneous) regression analysis on delegative leadership significantly influences achievement motivation, but only receives positive and significant support from the level of work and LMX. Likewise, in the fourth stage, the regression analysis on delegative (simultaneous) leadership had a substantial effect on continuous commitment, but only partially received positive and significant support from the conformity of the objectives. Therefore the findings in this study are leadership will be more productive with a delegative approach on the level of work and LMX to increase achievement motivation while increasing the continuous commitment of the leadership of the delegative, namely by making approaches to the fitness for purpose.